Karakteristik Budaya Indonesia pada Karakter Komik Nusa V - Aditia, Patra (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2020)
The development of Indonesian comics since the 1990s also raises questions about Indonesian identity itself. There are comics that prioritize the Indonesian side in terms of characterization, setting, theme, or terminology. One of the Indonesian comics that is quite interesting in this contemporary era is Nusa V. Nusa V by Sweta Kartika featuring five figures namely Rangga Wira Prakoso, Rimba Kala Manthana, George Saa, Kanaya Meuthia, and Renata Mokoginta. With Roland Barthes's semiotic theory approach which is aimed at examining the protagonists and the terms in the Nusa V universe, it can be concluded that Nusa V was created with the intention to create an Indonesian superhero that prioritizes local values ??but can still be accepted by global public. This is done by not making visualizations that are not too associated with local (Indonesian) values, but rather in a universal direction; Nusa V retains local values ??through the names of its protagonists, along with the terms of the terminology attached to them; Nusa V wants readers to be more interested in this comic based on Indonesian values ??and not referring to visual representation alone, and Nusa V wants to show the Archipelago aspect through terms derived from Sanskrit that are familiar with Hindu tradition in Indonesia. Keywords: Comics, Nusa V, Semiotics, Nusantara